Asymptotic methods in nonlinear wave phenomena : in honor of the 65th birthday of Antonio Greco, Palermo, Italy, 5-7 June 2006 - Ruggeri, Tommaso; Sammartino, Marco; Greco, Antonio M. (World Scientific, 2007)
This book brings together several contributions from leading experts in the field of nonlinear wave propagation. This field, which during the last three decades has seen important breakthroughs from the theoretical point of view, has recently acquired increased relevance due to advances in the technology of fluids e.g. at microscale or nanoscale and the recognition of crucial applications to the understanding of biological phenomena. Nonlinear wave theory requires the use of disparate approaches, including formal and rigorous asymptotic methods, Lie group theory, energy methods, numerical anal.